Covid-19 Adaptive Tourism Attraction: Tourism Resilience Through CHSE Certification For Visiting Decision - Wulandari, Dwi Pratiwi; Harmawan, Violintikha; Lisna, Yuke Permata; Mustika, Sari (Indonesian Journal of Tourism and Leisure, 2024)
CHSE (Cleanliness, Health, Safety, and Environment) certification is implemented by the Indonesian government to restore tourism conditions post-pandemic. The research aim is to analyze tourists' visiting decisions to visit COVID-19 adaptive tourist attractions after the implementation of the CHSE certification policy as a strategy to restore tourism conditions post-pandemic. There were no studies that investigated the effect of CHSE implementation on West Sumatra tourist attractions such as Taman Margasatwa dan Budaya Kinantan (TMBK) and Taman Panorama Lobang Jepang (TPLJ). The descriptive research was carried out with a causal-associative quantitative approach using 100 respondents.  The result revealed that: (1) The implementation of CHSE in COVID-19 is in the quite good category with a percentage of 50%. (2) Visiting decisions are in the quite good category with a percentage of 37.8%. (3) CHSE as a strategy to restore tourism conditions has an impact of 13.4% on visiting decisions. So, it is concluded that tourists decide to visit a COVID-19 adaptive tourist attraction, not solely because the tourist attraction has been CHSE certified. But 86.8% are influenced by other factors.